LIMS2 mutations are associated with a novel muscular dystrophy, severe cardiomyopathy and triangular tongues. (26th February 2015) - Chardon, Jodi Warman; Smith, A.C.; Woulfe, J.; Pena, E.; Rakhra, K.; Dennie, C.; Beaulieu, C.; Huang, Lijia; Schwartzentruber, J.; Hawkins, C.; Harms, M.B.; Dojeiji, S.; et al.
Abstract : Limb girdle muscular dystrophy (LGMD) is a heterogeneous group of genetic disorders leading to progressive muscle degeneration and often associated with cardiac complications. We present two adult siblings with childhood‐onset of weakness progressing to a severe quadriparesis with the additional features of triangular tongues and biventricular cardiac dysfunction. Whole exome sequencing identified compound heterozygous missense mutations that are predicted to be pathogenic in LIMS2 . Biopsy of skeletal muscle demonstrated disrupted immunostaining of LIMS2. This is the first report of mutations in LIMS2 and resulting disruption of the integrin linked kinase (ILK)–LIMS–parvin complex associated with LGMD.